2018
DOI: 10.1002/ece3.4004
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of fitness from energetics and life‐history data: An example using mussels

Abstract: Changing environments have the potential to alter the fitness of organisms through effects on components of fitness such as energy acquisition, metabolic cost, growth rate, survivorship, and reproductive output. Organisms, on the other hand, can alter aspects of their physiology and life histories through phenotypic plasticity as well as through genetic change in populations (selection). Researchers examining the effects of environmental variables frequently concentrate on individual components of fitness, alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 90 publications
(139 reference statements)
1
17
0
Order By: Relevance
“…In addition to reducing byssal thread structural integrity, elevated temperature decreased thread production. Living at 25°C is energetically costly to M. trossulus (Braby & Somero, 2006); thus, energy reserves may be shifted away from byssus production towards other processes (Carrington et al ., 2015; Sebens et al ., 2018). Previous studies on M. edulis found that thread production increases as temperature ranges from 2°C to 18°C (Moeser & Carrington, 2006; Moeser et al ., 2006; Young, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to reducing byssal thread structural integrity, elevated temperature decreased thread production. Living at 25°C is energetically costly to M. trossulus (Braby & Somero, 2006); thus, energy reserves may be shifted away from byssus production towards other processes (Carrington et al ., 2015; Sebens et al ., 2018). Previous studies on M. edulis found that thread production increases as temperature ranges from 2°C to 18°C (Moeser & Carrington, 2006; Moeser et al ., 2006; Young, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Because there are no published studies of maximum rates of population growth for blue mussels, we extended our literature search on this topic to include simulation and empirical studies for all marine and freshwater mussel species. Based on our findings from the literature for a diversity of mussel species (Jiao et al., 2008; Jones & Neves, 2011; Katsanevakis, 2009; Madenjian et al., 2010; Sebens et al., 2018), we were able to estimate an informative Gaussian prior for r , distributed as r z ~ Norm(0.21, 0.12 2 ). A similar, exponentially transformed prior was used for λ in the Beverton–Holt model.…”
Section: Methodsmentioning
confidence: 99%
“…The production of a structural biomaterial, however, requires an investment of energetic resources. The investment might result in energy allocation trade‐offs that shift performance traits on the individual level, and affect population dynamics (Sebens et al., 2018) and spatial distributions of organisms (biomechanical ecotype, Read & Stokes, 2006). For example, the altered growth and development of plants in response to wind or mechanical perturbation (thigmorphogenesis) reduces plant size and fecundity (Chehab et al, 2008; Telewski & Pruyn, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Filgueira et al., 2011; Nisbet et al., 2012), but differ in complexity and in their handling of uncertainty (Boersch‐Supan & Johnson, 2019). Energy budget models also provide a flexible framework with which to evaluate trade‐offs with structural materials since structural material production costs correlate with well‐described bioenergetic fluxes (Sanders et al., 2018; Sarà et al., 2013; Sebens et al., 2018), and can have different mass‐specific costs (Brody, 1945; Sanders et al., 2018). SFG models provide a simple conceptual framework where tissue growth is represented as a function of consumption of food minus physiological costs (Bayne et al., 1976; Sebens, 2002; Widdows & Bayne, 1971, Figure 1).…”
Section: Introductionmentioning
confidence: 99%